Impossible Justice and the Allure of the Absolute: A Psychoanalytic Reading of Radicalization - Sadeq Rahimi (Journal for Deradicalization)
This paper examines radicalization through the lens of contemporary psychoanalysis and social theory, challenging the dominant view of radicalization as a singular pathological transformation from a “normal” to an “abnormal” state. Instead, it conceptualizes radicalization as a psychosocial process embedded in subjective identity structures and broader historical conditions. Drawing on concepts such as subjectivity, the sinthome, split-thinking, hybridity, transitional spaces and hauntology, it highlights the psychological, emotional, and ideological mechanisms that make radical ideologies compelling. It explores how radicalized individuals construct meaning through rigid binaries, invest in utopian visions of justice, and develop cognitive patterns that resist moderation or alternative perspectives. Central to this framework is the psychoanalytic concept of the sinthome, which stabilizes subjective identity by providing coherence in the face of existential uncertainty. The discussion situates the appeal of absolute justice within the historical context of modernity’s breakdown and the impact of collective trauma and existential insecurity. The paper concludes by engaging with contemporary disengagement and deradicalization models, arguing that effective interventions must address not only ideological narratives but also the deeper psychological structures that sustain radical identities.